Observational Comparison between Confined and Eruptive Flares: Magnetohydrodynamics Instability Parameters in a Similar Magnetic Configuration - Kouhei Teraoka; Daiki Yamasaki; Yusuke Kawabata; Shinsuke Imada; Toshifumi Shimizu (The Astrophysical Journal)
Unstable states of the solar coronal magnetic field structure result in various flare behaviors. In this study, we compared the confined and eruptive flares that occurred under similar magnetic circumstances in the active region 12673, on 2017 September 6, using the twist number, decay index, and height of magnetic field lines to identify observational behaviors of the flare eruption. We investigated the parameters from the magnetic field lines involved in an initial energy release, which were identified from the positions of the core of flare ribbons, i.e., flare kernels. The magnetic field lines were derived by nonlinear force-free field modeling calculated from the photospheric vector magnetic field obtained by the Solar Dynamics Observatory SDO/Helioseismic and Magnetic Imager, and flare kernels were identified from the 1600 Å data obtained by the SDO/Atmospheric Imaging Assembly. The twist number of all the magnetic field lines in the confined flare was below 0.6; however, the twist number in seven out of 24 magnetic field lines in the eruptive flare was greater than 0.6. These lines were tall. It is found that the decay index is not a clear discriminator of the confined and eruptive flares. Our study suggests that some magnetic field lines in the kink instability state may be important for eruptive flares, and that taller magnetic field lines may promote flare eruption.